Use of recombinant activated factor VII in Jehovah's Witness patients with critical bleeding. (4th October 2012) - Kandane‐Rathnayake, Rangi K.; Isbister, James P.; Zatta, Amanda J.; Aoki, Naomi J.; Cameron, Peter; Phillips, Louise E.; ,; Dunkley, Scott; Houben, Roger; McNeil, John; Thomas, Wendy
Abstract Introduction The Australian and New Zealand Haemostasis Registry (ANZHR) included patients who received off‐licence recombinant activated factor VII (rFVIIa) for critical bleeding from 2000 to 2009. Approximately 1.3% of the ANZHR patients were Jehovah's Witnesses (JWs). We compared them with the non‐JW patients in the registry. Methods Patient characteristics (e.g. gender, context of bleeding), factors influencing rFVIIa use (e.g. body temperature and pH) and outcomes (e.g. bleeding response (stopped/attenuated or unchanged) to rFVIIa, mortality) were compared between JW and non‐JW patients using Fisher's exact chi‐square tests and Kruskal‐Wallis tests. Results A total of 42 JW and 3134 non‐JW patients were included in the analysis. Approximately 99% (n = 3098) of non‐JWs received blood products compared with only 30% (n = 13) of JWs (P < 0.01). The distribution of gender and contexts of critical bleeding in the two groups was significantly different. Approximately 17% of the non‐JW patients were hypothermic (T < 35°C) and about 19% were acidotic (pH < 7.2) at the time of initial rFVIIa administration. Conversely, none of the JWs were hypothermic and only one was acidotic. The proportion of positive responders to rFVIIa (stopped/attenuated bleeding following rFVIIa use) was similar in both groups (75% non‐JWs, 74% JWs; P = 1.0). Approximately 28% of non‐JW and 17% of JW patients were deceased by day 28 following rFVIIa use (P = 0.16). Discussion Several factors were observed to be significantly different between JW and non‐JW patients, yet the proportions of responders to rFVIIa were similar in both groups. The actual factors influencing response to rFVIIa are yet to be determined.